1970
DOI: 10.1104/pp.46.3.466
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Levels in Pea Seedlings Grown on Highly Salinized Media

Abstract: The levels of 18 enzymes were determined in leaves, stems, and roots of 11-day-old pea seedlings grown in a liquid medium or in the same medium containing, in addition, 5 atmospheres of either NaCl, KCI, Na2SO4, or K2SO4. Though the plants grown in saline media were stunted, the specific activities of the enzymes were the same in the given tissues of all plants. Also, the electrophoretic pattern of isozymes of malate dehydrogenase was not altered by growth of the plants in a saline medium. However, the isozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Furthermore, growth of Phaseolus and Atriplex in saline cultures failed to alter the specific activity, or NaCl sensitivity, of the enzymes studied. These data thus support and extend the observations of Weimberg (20,21). Weimberg found that different isozymes of malate dehydrogenase, isolated from various plant species, responded similarly to NaCl (20).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, growth of Phaseolus and Atriplex in saline cultures failed to alter the specific activity, or NaCl sensitivity, of the enzymes studied. These data thus support and extend the observations of Weimberg (20,21). Weimberg found that different isozymes of malate dehydrogenase, isolated from various plant species, responded similarly to NaCl (20).…”
Section: Discussionsupporting
confidence: 79%
“…Weimberg found that different isozymes of malate dehydrogenase, isolated from various plant species, responded similarly to NaCl (20). Moreover, Weimberg (21) showed that a variety of salinity treatments failed to alter the specific activity of many enzymes and the isoenzyme patterns of malate dehydrogenase in pea leaf, stem, and root. The data conflict with those of Porath and Poljakoff-Mayber (6,16,17), who reported that two of the in specific activity to NaCl and Na2SO, salinity in pea root.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The action of asparaginase yields NH4' and aspartate, which together with imported aspartate could provide the C4 unit for export as a number of C4-dicarboxylic acids (24). The maximal activities of both aspartate and alanine aminotransferases in seedcoat cells (Table I) are the highest of any tissue of the pea plant (8,27).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity damages soil structure and decreases the productivity of most crops as plant growth is affected in several aspects of its metabolism. These include photosynthesis (Nieman and Clark, 1976), osmotic adjustment (Bernstein, 1963), nutritional imbalance and specific ion toxicity (Cordovilla et al, 1994;Gunes and Alpaslan, 1996;Jacoby, 1999), ion uptake (Greenway et al, 1966), enzyme activities (Weimberg, 1970), protein and nucleic acid synthesis (Nieman, 1965), photosynthesis (Downton, 1977), and hormonal balance (Itai et al, 1968). Salinity also reduces growth rate by reducing the uptake of water by plants (Munns, 1993;Munns, 2002).…”
Section: Introductionmentioning
confidence: 99%